Processos de comunicação da disciplina Cálculo I do curso de licenciatura em Matemática na modalidade a distância do CESAD/UFS/UAB - Santos, Márcio Batista (2012)
This dissertation follows the analysis of communication processes established in the discipline Calculus Differential and Integral I of course degree in mathematics at the Center for Distance Higher Studies, Federal University of Sergipe, partner institution of the program Open University of Brazil. This is a qualitative research, case study with a phenomenological approach, with the use of elements ethnographic. The subjects were students, tutors and teacher discipline coordinator bound to Calculus I course in the school period 2010/2 of that institution. The dissertation focused on the following problem: how were established communication processes between the group tutor-student- teacher discipline coordinator in the context of the Calculus I discipline and how it interfered in the process of teaching and learning of this group. We tried to build a clash of ideas from studies of Vygotsky (1991, 1996), Morin (2005, 2009, 2010) and Peters (2003, 2004) regarding communication and interrelationships with the teaching and learning. In view of the aspects analyzed the study pointed out that the processes of communication between subjects occurred in a discontinuous manner and in the case of student-tutor occurred via e-mail or individual messages, and that the guidelines were articulated from written language only, so you could see that some of the difficulties with regard to learning content was related to the difficulties presented in the displacement of a teaching-learning developed from language "spoken " trampled to another predominantly written language. Due to this fact, some students have resorted to private tutors not linked to the UAB program. Another point worth mentioning is that the efficiency in relation to communication processes established between students-teachers- cut across the responsibilities of persons involved and into the limits of the tasks of a number of professionals who advised.